The Effect of Tax Education on Taxpayer Compliance - Amelia, Fatimah Rizky; Harefa, Irwan; Putra, Yananto Mihadi (Baca Dulu Publisher, 2025)
Taxpayer compliance is a crucial issue for Indonesia, considering that taxes form the nation's fiscal backbone, contributing over 70% to the state budget (APBN). Despite ongoing government reforms, compliance rates remain suboptimal, and revenue collection often falls short of targets. Within the self-assessment system, which demands voluntary awareness, tax education has become a primary strategy for the Directorate General of Taxes (DJP). This study aims to analyze the influence of tax education—both traditional, through face-to-face counseling, and digital, through social media and online platforms—on taxpayer compliance. The method employed is a literature review, examining various scientific journals and other relevant sources. The analysis of previous studies consistently reveals that tax education has a positive and significant influence on taxpayer compliance. An improved understanding of taxpayer rights and obligations is proven to foster both formal and material compliance.